PENGARUH NET PROFIT MARGIN (NPM) DAN RETURN ON ASSETS (ROA) TERHADAP HARGA SAHAM - Mohamad Fazar Fadilah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The aim of this study is to determine whether the Net Profit Margin (NPM) and Return on Assets (ROA) have an impact on the stock price. The research population is a Food and Beverage company listed on the Indonesian Stock Exchange. The total sample used in this study was 8 companies. Purposive sampling is used as a sample-taking technique. The research was conducted using quantitative methods, and the data source came from the corporate financial statements. Data analysis was done using double linear regression analysis in the SPSS version 25 computer program. This research shows that NPM has a partial influence on the price of the stock, but ROA has no effect on the stock price. Simultaneously, NPM and ROA have no significant influence over the stock prices